Investigation of the effect of disulfiram on corrosion of mild steel in hydrochloric acid solution - Singh A.K.; Quraishi M.A. (My University, 2025)
The corrosion inhibition properties of disulfiram (DSR) for mild steel in HCl solution were analyzed by electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, atomic force microscopy, scanning electron microscopy and gravimetric methods. Physical adsorption is proposed for the inhibition and the process followed the Langmuir adsorption isotherm and kinetic/thermodynamic model of El-Awady et al. Constant phase elements describing the non-ideal characteristics of the electrochemical interface are introduced. The occurrence of inductive loop is also dealt with, through the introduction of an inductive element L. The use of these elements significantly improved the quality of fit of simulation to the EIS data. © 2011 Elsevier Ltd.